A QUALITATIVE STUDY OF CLASSROOMSCREEN USE IN RECOUNT TEXT LEARNING AT JUNIOR HIGH SCHOOL: A REFLECTIVE PRACTICE - Widyapsaridhanti, Maystika Tsamara (JURNAL SOCIUS, 2025)
This study aimed to explore the teacher’s experience in using the digital media ClassroomScreen in teaching recount texts to eighth-grade junior high school students, as well as to identify its impact on students’ learning processes. The background of this research was based on the low motivation and engagement of students in understanding recount texts, along with the limited use of interactive learning media that support classroom management and active participation. A descriptive qualitative approach was employed, using a reflective study design. Data were collected through participatory observation, field notes, and visual documentation during the learning process. The data were analyzed using Miles’ interactive model and Gibbs’ Reflective Cycle. The findings show that the use of ClassroomScreen provides a positive experience for teachers in managing the class and delivering material visually and systematically, while also promoting reflection on teaching practices. For students, the media increases engagement, motivation, learning discipline, and ability to understand and write recount texts. Features such as the timer, work symbols, and random name picker are effective in creating a more orderly and enjoyable learning environment. However, some challenges were also encountered, including students’ gaps in digital literacy and limited technological infrastructure. This study recommends the use of simple yet functional digital media in learning, supported by training for both teachers and students. The findings are expected to be a reference for educators and policymakers in developing reflective and contextual technology-based learning strategies.